Cardiovascular disease attenuates the protective effect of folate on global cognitive function in an elderly population: a cross-sectional study - Jianqiang Zhang; Di Yue; Huifeng Zhang (Scientific Reports)
Abstract Research suggests that folic acid contributes to improving cognitive function. However, there is a lack of systematic research on the association of dietary intake of folate and serum, and red blood cell (RBC) folate levels with global cognitive impairment (CoI) in the elderly population. Importantly, excessive supplementation with folate among American adults at high risk of cardiovascular disease (CVD) may have harmful effects. CVD often leads to worse cognitive function; therefore, it is necessary to explore the characteristics of the association of folate with CoI in both CVD and non-CVD populations. Participants aged ≥ 60 years from the national health and nutrition examination survey (NHANES) 2011–2014 were included. Dietary intake of folate and serum and RBC folate levels were determined through questionnaires or laboratory measurements. Global cognitive function was assessed via the results of three cognitive assessments. Multivariable logistic regression and restricted cubic splines (RCS) were employed to assess the odds ratios (ORs), 95% confidence intervals (CIs), and potential non-linearities of folate with cognition. Additionally, the interaction term of CVD with RBC folate was included in the model, and effect modification was detected through likelihood ratio tests. Finally, several sensitivity analyses were conducted to validate our findings. This study included 2104 participants with complete data and a median age of 68 years, with females comprising 51% of the participants. Of the participants, 444 individuals were defined as having CoI. In the NHANES, Pearson correlation analysis revealed moderate to weak correlations between dietary, serum, and RBC folate levels and CoI (all < 0.6). In addition, when different sources of folate were included separately in the models, fully adjusted logistic regression with continuous variables included in the model revealed that only RBC folate was significantly associated with CoI [odds ratio (OR) 0.86, 95% confidence interval (95% CI) 0.75–0.97, P = 0.02]. According to tertile groups, compared with participants in the lowest tertile, individuals in the highest tertile of total dietary folate levels (OR 0.67, 95% CI 0.48–0.94, P = 0.02), folic acid levels (OR 0.57, 95% CI 0.38–0.86, P = 0.01), and RBC folate levels (OR 0.62, 95% CI 0.44–0.85, P = 0.004) had significantly lower odds of having CoI. The RCS showed a linear negative correlation between RBC folate levels and CoI. Furthermore, interaction analysis suggested that CVD attenuated the protective effect of RBC folate. Several sensitivity analyses also suggested a modifying effect of CVD on the association between RBC folate and CoI. A significant negative correlation exists between RBC folate levels and CoI in the elderly population of the United States, and this association is stronger than that of other folate measures. However, the protective effect of RBC folate on CoI is negated in patients with CVD, and further investigation is needed to explore the underlying mechanisms involved.